(untitled) (Jurnal Wahana Konseling, 2023)
Aggressiveness is an act committed by an individual with the intention of hurting oneself, other people, or other objects. Some students of SMPN 17 Malang who have a habit of behaving aggressively need to be given individual counseling services in order to inhibit their aggressive behavior. Many techniques in guidance and counseling can be used to reduce aggressive behavior in students. One of them is the behavioral aversion technique approach. This study aims to reduce the aggressive behavior of SMPN 17 Malang students through behavioral counseling with aversion techniques. This study included a pre-experimental design with One Group Pretest-Posttest, the research subjects were 3 students who had high aggressive behavior, which was measured using an aggressive behavior scale. The results of the Wilcoxon test showed a significance value greater than 0.05. Because this research is to reduce behavior, the researcher uses an inverse significance value benchmark, meaning that if the significance value is greater than 0.05, this research is considered effective. So it can be concluded that behavioral counseling uses effective aversion techniques to reduce aggressive behavior in students. In future research, it is expected to be able to develop aversion techniques in more detail and better as well as a reference material to help overcome the problems of other subjects who need guidance and counseling services both individually and in groups.